Potential exports and nontariff barriers to trade Sri Lanka national study. (Potential exports and nontariff barriers to trade.)
It examined Sri Lankan export products which have the potential to increase their market share in Bangladesh, Bhutan, India, Maldives, and Nepal. Options and opportunities to deal with identified nontariff barriers are considered, including legal reforms, upgrade of quality standards and the requisite laboratory equipment and instruments, and institution building of both accrediting bodies and conformity assessment bodies. Practical recommendations for action by both public and private sectors propose an effective way forward.